Uniform family code : the proposal of Bangladesh Mahila Parishad - Nabi, Bela (Bangladesh Mahila Parishad, 2015)
Contributed articles and recommendations for reform and amendments of laws concerning rights of women and uniform family code in Bangladesh as envisaged by the Bāṃlādeśa Mahilā Parishada, or Bangladesh Women Council, during a series of workshops held at various locations countrywide.